Pemahaman Konsep Konseling Dan Keterampilan Dasar Konseling Pada Mahasiswa Kelas Konseling Traumatik - Perianto, Eko; Purwaningrum, Shinta (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Understanding of Counseling Concepts and Basic Counseling Skills for Traumatic Counseling Class Students. This study aims to determine students' understanding of the concept of counseling and basic counseling skills in traumatic counseling class students in the Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Universitas PGRI Yogyakarta. This research is a population study, where the research subjects are taken from the total number of trauma counseling classes, which are 30 (thirty) people. The data collection technique used in this research is a questionnaire. Data analysis in this study is to use descriptive statistics with percentage techniques, namely statistics that function to describe or provide an overview of the object under study. The results showed that first, the students' understanding of the traumatic counseling class in the guidance and counseling study program was in the High category. Second, students' understanding of basic counseling skills as the basis for carrying out the practice of traumatic counseling activities is in the high category. For further researchers, they can develop and examine other variables related to the abilities that must be possessed by students of the guidance and counseling study program as prospective school counselors.Keywords: Understanding, Counseling, Students